Training load quantification in a Norwegian professional football team: Within and between microcycle comparisons - Dalen-Lorentsen, T.; Ronneberg, K. L.; Luteberget, L. S. (Sport Performance & Science Reports, 2022)
Practitioners are constantly trying to appropriately manip ulate training content to optimize training outcomes and competitive performance (1,2), as well as mitigating injury risk (3,4). Players must maintain a sufficient training stimulus to keep fit throughout the season, so practitioners must find an optimal balance between loading and freshness before the up coming match, as well as a risk vs reward towards injury risk. Research on how training load fluctuates within and between microcyles across a full season could be of use for practitioners aiming to further their understanding of the training planning process.